STRATEGI PENINGKATAN KINERJA GURU YANG PROFESIONAL - Amna Emda (UIN AR-RANIRY, 2016)
Education Implementation success is determined by the readiness of hearts teachers prepare their students participants through Teaching and Learning Activities . Good Quality Education For Being benchmarks of success is shown by the boarding costs . teacher. The creation of the Good boarding costs if someone has a teacher Personality And Dedication And Able to telecom - telecoms professionalism Learning hearts . Increased costs kos teacher can be done through development professionalisme.